Quem constrói as casas: entre as gavetas e o labirinto dos arquivos - Maria Figueiredo Vaz (2022)
This research focuses on the creations of contemporary Brazilian artists starting from the rescue and appropriation of family and public archives, bringing a reflection on memory, imagination and the power of the personal domain to point to the collective. With an emphasis on family photographic archives, it takes place within a dialogic structure, in a conversation not only between images and works, but between those who form them. The conversations and approximations with the artists and works incorporated into the proposed cut are brought, through a poetic and literary language, by the houses of each one, in an attempt to bring together and amalgamate the construction of memory to the construction of the lived space itself. Thus, this is not traditional analytical research, but a critique elaborated through dialogue, understanding the dimension of affections and relationships that allow multiple forms of constitution and appropriation of family archives. Finally, the research is based on the artistic work of self-authorship, conducted by the archives - photographs, letters, reports - and memories of the author's maternal grandmother, Jacy, and by the question that names the research - "who builds the houses?”.